2013
DOI: 10.1673/031.013.3601
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of the Japanese Beetle,Popillia japonica, in Soybean Fields

Abstract: The Japanese beetle, Popillia japonica Newman (Coleoptera: Scarabaeidae), is a serious pest of many agricultural and horticultural plants. Relatively little research has investigated the distributions of Japanese beetles in agricultural fields, and this lack of information makes pest management more difficult. In the present study, the spatial distribution of Japanese beetles in soybean fields was examined. Specifically, how the distribution and abundance of beetles was affected by distance from an edge, edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…citri . Similar edge effects have been observed in the spatial distribution of the Japanese beetle, Popillia japonica Newman (Coleoptera: Scarabaeidae) with higher beetle densities observed on edges of soybean fields than field interior, and specifically downwind hedges harbored more beetles than the other edges [ 25 ].…”
Section: Discussionsupporting
confidence: 54%
“…citri . Similar edge effects have been observed in the spatial distribution of the Japanese beetle, Popillia japonica Newman (Coleoptera: Scarabaeidae) with higher beetle densities observed on edges of soybean fields than field interior, and specifically downwind hedges harbored more beetles than the other edges [ 25 ].…”
Section: Discussionsupporting
confidence: 54%
“…We also observed temporal variations in larval and beetles abundance, with high numbers in farmyard manure treated plots. Sara et al ( 2013 ) suggested that spatial activities of beetles are greatly influenced by change in habitat. Adults and white grubs of green jute beetle were reported to be attracted to the field fertilized with farmyard manure from cow and poultry (Diagne 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sara et al. () found adult density decreased significantly with increasing distance from a field edge.…”
Section: Pest Categorisationmentioning
confidence: 98%